Prevalence and factors associated with depression among cancer patients attending chemotherapy at Jimma University Medical Centre, Jimma, Southwest Ethiopia - Melkamu Gelan Negesa; Tariku Bekala Gadisa; Kebenesa Angasu Kitaba; Bikila Dereje Fufa (Elsevier, 2024)
Background: Cancer is a chronic, life-threatening disease that causes depression, stigma, and economic cost in developing countries and most common mental problem among cancer patients on chemotherapy. Objectives: To assess the prevalence and factors associated with depression among cancer patients attending chemotherapy at JUMC. Methods: An institution-based cross-sectional study was conducted. A simple random sampling method was used to select 300 participants and they were interviewed from March 01 to April 01, 2022. Data was collected by using a pretested questionnaire and patient card review. The collected data were coded and entered into Epi Data Manager 4.6 and SPSS version 26 was used for analysis. Those variables with a p-value of 0.25 were candidates for multivariable logistic regressions with a p-value of 0.05, and the association was finally determined by a 95% confidence interval. Result: The prevalence of depression was 170 (56.6 %), (95 % CI = 50.92, 62.28). Patients who live in urban (AOR = 0.47, 95 % CI: 0.29, 0.78), chewing khat (AOR = 2, 95 %CI: 1.17, 3.53), patients on their first chemotherapy (AOR = 2.8, 95 %CI: 1.17, 6.64), on the second chemotherapy cycles (AOR = 3.51, 95 %CI: 1.57, 7.60), and duration starting chemotherapy for 1-3 months (AOR = 0.36, 95 %CI: 0.18, 0.72) were significantly associated with depression. Conclusion and Recommendation: According to the findings of this study, depression was highly prevalent among patients on chemotherapy so Jimma Medical Centre should give awareness creation and health education about cancer for the rural community, risks of chewing khat, chemotherapy treatment, and duration of starting chemotherapy.